'College for all' in Anglophone countries – meritocracy or social inequality? An Australian example. Issue 1 (2nd January 2016) - Wheelahan, Leesa
Abstract : This article analyses the expansion of higher education offered by technical and further education institutes in Australia and it compares this provision with the expansion of higher education in further education colleges in England, and baccalaureate degrees in community colleges in the United States. It argues that this provision can open new opportunities for students, while at the same time contributing to social inequality because not all types of higher education are equal. It uses Trow's typology of elite, mass and universal higher education to analyse this expansion, and it uses social realism to discuss whether 'applied' higher education provides students with similar opportunities to students in more elite institutions. It draws from two related research projects in Australia that researched the growth of higher education in institutions outside universities to explore these issues.